ENSURING PEDAGOGICAL AND PSYCHOLOGICAL COMPATIBILITY IN CONTINUOUS EDUCATION IS THE BASIS OF THE EFFECTIVENESS OF INCLUSIVE EDUCATION - Kobilova Shaxnoza Xudayshukurovna (Bright Mind Publishing, 2025)
This article provides a scientific discussion on the safety of the inclusive education space, the need for a healthy socio-psychological environment in the school where a student with disabilities is studying, inclusive education standards, regulatory and legal framework, and special pedagogical and psychological knowledge and skills to organize the content of continuous inclusive education to ensure its safety.
Keywords: Student with disabilities, teaching and upbringing, inclusive practice, educational institution, psychological and pedagogical support, special knowledge and skills, specialist, teacher and assistant specialists, implementation of inclusive education.